TATALAKSANA PASIEN STOMATITIS AFTOSA REKUREN MINOR DENGAN FAKTOR PREDISPOSISI ANEMIA NORMOSITIK - Ivan Hasan; Ahmad Ronal; Audiawati Surachmin; Nurfianti (Lembaga Penelitian Universitas YARSI, 2025)
Recurrent aphthous stomatitis (RAS) is an ulcerative lesion of the oral mucosa that often recurs and can be triggered by various factors, including stress and systemic conditions such as anemia. Hyperproliferative normocytic anemia, which can be caused by acute bleeding or hemolysis, contributes to the appearance of oral manifestations such as RAS, glossitis, angular cheilitis, and pale mucosa. This report presents a case of a 24-year-old female patient who experienced recurrent RAS related to stress and menstrual cycles, accompanied by indications of anemia. Management was carried out holistically with a combination of local therapy (topical corticosteroids and antiseptics), iron supplementation, and patient education regarding triggering factors and oral health care. The results show the importance of identifying and treating predisposing factors to reduce RAS recurrence and improve patient quality of life.